Hexagonal boron nitride: Epitaxial growth and device applications. (March 2021) - Maity, A.; Grenadier, S.J.; Li, J.; Lin, J.Y.; Jiang, H.X.
Abstract: As a newest family member of the III-nitrides, BN is considered amongst the remaining frontiers in wide energy bandgap semiconductors with potentials for technologically significant applications in deep UV (DUV) optoelectronics, solid-state neutron detectors, electron emitters, single photon emitters, switching/memory devices, and super-capacitors. It was shown that it is possible to produce h-BN epilayers with high hexagonal phase purity, UV transparency, and film stoichiometry by employing nitrogen-rich growth conditions. The quasi-2D nature of h-BN supports unusually strong optical transitions near the band edge and a large exciton binding energy on the order of 0.7 ​eV. Due to the fact that the isotope of B-10 has a large capture cross-section for thermal neutrons, h-BN is an ideal material for the fabrication of solid-state neutron detectors for special nuclear materials detection, well and geothermal logging, and medical imaging applications. Freestanding B-10 enriched h-BN (h- 10 BN) epilayers with varying thicknesses up to 200 ​μm have been successfully synthesized by metal organic chemical vapor deposition (MOCVD) as of this writing. By utilizing the conductivity anisotropy nature of h-BN, 1 ​cm 2 lateral detectors fabricated from 100 ​μm thick h- 10 BN epilayers have demonstrated a detection efficiency of 59% for thermal neutrons, which is the highest on record among all solid-state neutron detectors as of today. It was noted that high growth temperatures, long growth times and the use of sapphire substrate tend to incorporate oxygen related impurities into h- 10 BN epilayers, which strongly impacted the carrier mobility-lifetime (μτ) products and charge collection efficiencies of h- 10 BN neutron detectors. As the h-BN material technology further develops, improved carrier mobilities and μτ products will allow the fabrication of h-BN devices with enhanced performance.